Sizing the Holin Lesion with an Endolysin-β-Galactosidase Fusion - Wang, Ing-Nang (American Society for Microbiology, 2003)
Double-stranded DNA phages require two proteins for efficient host lysis: the endolysin, a muralytic enzyme, and the holin, a small membrane protein. In an event that defines the end of the vegetative cycle, the λ holin S acts suddenly to permeabilize the membrane. This permeabilization enables the R endolysin to attack the cell wall, after which cell lysis occurs within seconds. A C-terminal fusion of the R endolysin with full-length β-galactosidase (β-Gal) was tested for lytic competence in the context of the late-gene expression system of an induced λ lysogen. Under these conditions, the hybrid R-β-Gal product, an active tetrameric β-Gal greater than 480 kDa in mass, was fully functional in lysis mediated by the S holin. Western blot analysis demonstrated that the lytic competence was not due to the proteolytic release of the endolysin domain of the R-β-Gal fusion protein. The ability of this massive complex to be released by the S holin suggests that S causes a generalized membrane disruption rather than a regular oligomeric membrane pore. Similar results were obtained with an early lysis variant of the S holin and also in parallel experiments with the T4 holin, T, in an identical lambda context. However, premature holin lesions triggered by depolarization of the membrane were nonpermissive for the hybrid endolysin, indicating that these premature lesions constituted less-profound damage to the membrane. Finally, a truncated T holin functional in lysis with the endolysin is completely incompetent for lysis with the hybrid endolysin. A model for the formation of the membrane lesion within homo-oligomeric rafts of holin proteins is discussed.